Before and after : user's knowledge maturity within personal information management. - Kamaruddin, Azrina; Admodisastro, Novia; Dix, Alan (Research Publication, 2013)
Personal Information Management (PIM) is an important discipline that evolves with the technology advancements in their operating systems.The understanding of its four main activities in PIM : organizing, retrieving, deleting and archiving are crucial because the information growth in our desktop increased overtime. The paper presents the study conducted to enhance understanding of one of the causes for core phenomena–user’s knowledge maturity which was identified in prior studies . The qualitative approach is taken to deepen our understanding on this cause. As a result, we found that several issues pertaining to time and users’ task have increased their knowledge on organizing-keeping information on their desktop.